Leader-Member Exchange, Sense of Community, Counterproductive Work Behavior, and Pararem on Business Sustainability - Kasih, Ni Luh Sri; Riana, I Gede; Dewi, I Gusti Ayu Manuati; Wibawa, I Made Artha (Universitas Pendidikan Ganesha, 2025)
This study developed an integrated research model to examine the relationship between Leader-Member Exchange (LMX), Sense of Community, Counterproductive Work Behavior (CWB), and Pararem on business sustainability within Village Credit Institution (Lembaga Perkreditan Desa—LPD) in Bali. The research was driven by the need to explore how leadership dynamics, organizational culture, and traditional Balinese regulations influence the sustainability of community-based financial institutions. A qualitative approach was employed using content analysis of academic literature sourced through the Google Scholar database. The analysis was grounded in dynamic capability theory, leader-member exchange theory, and social exchange theory to explain how internal and cultural mechanisms affect business continuity. The results indicated that high-quality LMX and a strong sense of community played a crucial role in reducing CWB. Furthermore, adherence to Pararem—a traditional Balinese regulatory framework—reinforced organizational discipline and cohesion, contributing positively to long-term sustainability. The study provided theoretical contributions by bridging Western organizational theories with local cultural practices. It also offered practical implications for LPD leaders and policymakers in enhancing governance structures and promoting ethical conduct. By synthesizing cross-disciplinary perspectives, this research underscored the importance of integrating formal leadership strategies with indigenous values to strengthen institutional resilience in the Balinese context.